2023
DOI: 10.3390/molecules28031068
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape of Methods to Evaluate Antimicrobial Activity of Natural Extracts

Abstract: Natural extracts have been and continue to be used to treat a wide range of medical conditions, from infectious diseases to cancer, based on their convenience and therapeutic potential. Natural products derived from microbes, plants, and animals offer a broad variety of molecules and chemical compounds. Natural products are not only one of the most important sources for innovative drug development for animal and human health, but they are also an inspiration for synthetic biology and chemistry scientists towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…The extract obtained presented a MIC of 1.5 mg/mL against S. aureus and 2.0 mg/mL against S. epidermidis . The MIC obtained in this study proved to be much higher than that of the propolis evaluated in other regions of the world, such as those reported in [ 73 ], where propolis extracts obtained from Algeria (eastern zone) were studied, with MICs of 0.04 and 0.06 mg/mL against S. aureus and S. epidermidis , respectively [ 74 , 75 , 76 , 77 ]. Different types of antimicrobial synthetic and natural compounds have been described, as well as specific active mechanisms and MIC levels [ 74 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The extract obtained presented a MIC of 1.5 mg/mL against S. aureus and 2.0 mg/mL against S. epidermidis . The MIC obtained in this study proved to be much higher than that of the propolis evaluated in other regions of the world, such as those reported in [ 73 ], where propolis extracts obtained from Algeria (eastern zone) were studied, with MICs of 0.04 and 0.06 mg/mL against S. aureus and S. epidermidis , respectively [ 74 , 75 , 76 , 77 ]. Different types of antimicrobial synthetic and natural compounds have been described, as well as specific active mechanisms and MIC levels [ 74 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 54%
“…The MIC obtained in this study proved to be much higher than that of the propolis evaluated in other regions of the world, such as those reported in [ 73 ], where propolis extracts obtained from Algeria (eastern zone) were studied, with MICs of 0.04 and 0.06 mg/mL against S. aureus and S. epidermidis , respectively [ 74 , 75 , 76 , 77 ]. Different types of antimicrobial synthetic and natural compounds have been described, as well as specific active mechanisms and MIC levels [ 74 , 75 , 76 , 77 ]. However, due to the complexity and variety of the compositional matrix found in propolis, there is no established level of MIC to use as an antimicrobial agent.…”
Section: Resultsmentioning
confidence: 54%
“…In the evaluation of antimicrobial activity in honey samples, certain considerations must be taken in attention due to the complex matrix of this type of biological sample and the main goal of the experimental settings (see Table 5). In fact, several studies have already reported the benefits and drawbacks of several microbiological techniques applied in honey samples (Balouiri et al., 2016; Gonzalez‐Pastor et al., 2023; Hossain, Lim, et al., 2022). As previous reported by Hossain, Lim, et al.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the bacteriostatic effect of Cu-CCDs against S. aureus and E. coli , the operational steps were as follows [ 57 ]. In total, 50 μL of S. aureus and E. coli suspension (1 × 10 8 CFU/mL) and 5 mL of LB broth were incubated with different concentrations (5, 2.5, 2.25, 2, and 1 μg/mL) of Cu-CCDs solution at 37 °C for 12 h. After this, 100 μL of culture solution was dispersed onto LB nutrient agar plates and incubated at 37 °C for 24 h to observe colony formation.…”
Section: Methodsmentioning
confidence: 99%